Utility of the Phenacyl Protecting Group in Traceless Protein Semisynthesis through Ligation–Desulfurization Chemistry. Issue 1 (9th January 2018) - Matveenko, Maria; Hackl, Stefanie; Becker, Christian F. W.
Abstract: Semisynthesis of proteins via expressed protein ligation is a widely applicable method, even more so because of the possibility of ligation at non‐cysteine sites using β‐mercapto amino acids that can be converted to the corresponding native amino acids by desulfurization. A drawback of this ligation– desulfurization approach is the removal of any unprotected native cysteine residues within the ligated protein segments. Here, we show that the phenacyl (PAc) moiety can be successfully used to protect cysteines within recombinantly generated protein segments. As such, this group was selectively appended onto cysteine side chains within bacterially expressed polypeptides following intein cleavage, which reveals a rather sensitive thioester at the C‐terminus. The PAc group proved to be compatible with native chemical ligation, radical desulfurization, and reverse‐phase HPLC conditions, and was smoothly removed at the end. The utility of the PAc protecting group was then demonstrated by the 'traceless' semisynthesis of two proteins containing one or two native cysteines: human small heat shock protein Hsp27 and murine prion protein. Abstract : Keeping the cysteines : During protein semisynthesis, parts of the sequence are produced recombinantly and may contain one or several cysteine residues that are compromised by the radical desulfurization reaction that follows ligations at non‐native cysteine or other beta‐thiol amino acids. Here, native cysteines are protected at the appropriate stage of the synthesis and successfully revealed at the end to obtain homogeneous proteins.